The butyrylcholinesterase K variant and susceptibility to Alzheimer's disease. - Kehoe, P; Williams, H; Holmans, P; Wilcock, G; Cairns, N; Neal, J; Owen, M (1998)
Previous work has shown an association between the K variant of the butyrylcholinesterase (BCHE) gene and Alzheimer's disease (AD) in patients carrying the epsilon4 allele of ApoE. We attempted to replicate this finding in 181 UK white AD cases and 71 controls. No difference was found in BCHE-K genotypes (p=0.75) or alleles (p=0.70) between patients and controls. Moreover, despite a significant excess of ApoE epsilon4 in patients versus controls (p<0.0001), we found no evidence to support previous reports of an interaction between ApoE and BCHE-K (chi2=1.49, df=4, p=0.83).